A. Cancellier; A. Cassani; L.A. Messina Fajardo; G. Scocozza; D. Winkler (a cura di) "Lingue, linguaggi e politica" - Andrés Ortega Garrido (Cuadernos AISPI)
Antonella Cancellier; Alessia Cassani; Luisa A Messina Fajardo; Giovanna Scocozza; Dagmar Winkler (a cura di), "Lingue, linguaggi e politica", Padova, CLEUP, 2019, 668 pp. ISBN: 9788854950856.